Method for detecting carbon coating integrity of lithium iron phosphate material
By measuring the conductivity, coating thickness and specific surface area of lithium iron phosphate material, and calculating the cladding integrity index, the problem of insufficient comprehensiveness and high cost in the prior art is solved, and high efficiency of lithium iron phosphate material is achieved. Accurate evaluation improves the efficiency of material screening and battery performance evaluation.
Patent Information
- Application Number
- CN202411266881.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-31
AI Technical Summary
The existing methods for detecting carbon coating thickness and coating integrity of lithium iron phosphate materials rely on electron microscope equipment. The test is not comprehensive enough, the equipment and operator technical requirements are high, the cost is high, and the overall performance of the material cannot be effectively evaluated.
By measuring the conductivity, coating thickness and specific surface area of lithium iron phosphate material, the coating integrity index R is calculated, and combining carbon content and conductivity, it provides a simple and accurate evaluation method, reducing the equipment and operators' Reliance improves detection efficiency and accuracy.
Through simplified mathematical calculations, this method provides clear evaluation standards, reduces the influence of subjective factors, improves the efficiency and accuracy of material screening, and significantly improves the evaluation efficiency and quality. It is suitable for evaluating and screening lithium iron phosphate materials. Evaluate the advantages and disadvantages of the battery production process.
Smart Images

Figure CN119224060A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of material detection, and in particular to a method for detecting the integrity of carbon coating of a lithium iron phosphate material. Background Art
[0002] Lithium iron phosphate (LiFePO4, LFP for short) has become a widely used positive electrode material for lithium-ion batteries due to its safety, reliability, abundant raw material sources, high theoretical specific capacity, and good cycle performance. However, the LFP material itself has some disadvantages, such as low electronic conductivity and ion diffusion rate, which greatly limit its charge and discharge rate and capacity performance at high rates. Currently, the common way to improve these problems is mainly carbon coating. The main functions of carbon coating include:
[0003] 1. Improve electronic conductivity: Carbon is a good conductor. Carbon coating can form a conductive network on the surface of LFP particles, thereby improving the electronic conductivity of the entire electrode material.
[0004] 2. Promote lithium ion diffusion: Appropriate carbon coating can reduce the contact resistance between LFP particles and facilitate the rapid diffusion of lithium ions.
[0005] 3. Enhanced structural stability: The carbon coating can help maintain the structural integrity of LFP particles during the charge and discharge process, reducing the possibility of particle breakage or agglomeration.
[0006] 4. Improve interface properties: Carbon coating can optimize the interface properties between LFP and electrolyte, reduce the occurrence of side reactions, and thus improve the overall performance of the battery.
[0007] The thickness and integrity of the carbon coating layer of the LFP material have a direct impact on the above effects. Incomplete carbon coating will inevitably lead to a significant reduction in the carbon coating effect. Too thin or even no coating area may not effectively improve the conductivity or protect the LFP particles, while too thick carbon coating will increase the ineffective mass, reduce the energy density, and may hinder the transmission of lithium ions. Therefore, the characterization of the thickness and integrity of the carbon coating layer of the LFP material is an important means to screen and evaluate the positive electrode material and determine the quality of the subsequent cycle of the lithium-ion battery.
[0008] At present, the evaluation of the thickness and integrity of the carbon coating of LFP materials is mainly based on electron microscope equipment and reverse analysis of the battery's later cycle performance. The analysis of the thickness and integrity of the carbon coating of lithium iron phosphate materials is also only based on electron microscope equipment. Only some particles can be selected for analysis during the test, and the evaluation is not comprehensive enough. In addition, the equipment capability requirements as well as the operator's experience and technical requirements are high, and the testing costs are large. Summary of the invention
[0009] The technical problem to be solved by the present invention is to provide a method for detecting the integrity of carbon coating of lithium iron phosphate material.
[0010] In order to solve the above technical problems, the technical solution of the present invention is:
[0011] A method for detecting the integrity of carbon coating of lithium iron phosphate material, the specific steps are as follows:
[0012] (1) Determine the conductivity σ (S / m) of the LFP powder sample to be tested;
[0013] (2) Determine the coating thickness d (nm) of the LFP powder sample to be tested;
[0014] (3) Calculate the LFP material coating integrity index R according to the following formula: R = σ / d;
[0015] (4) The LFP material was evaluated based on the calculation results. The larger the R value, the better the material coating integrity.
[0016] Preferably, in the above-mentioned method for detecting the integrity of carbon coating of lithium iron phosphate material, the coating layer thickness d in step (2) is a theoretical coating layer thickness d, which is obtained by the following method:
[0017] (1) Determine the carbon content C% of the LFP powder sample to be tested;
[0018] (2) Determine the specific surface area S (cm) of the LFP powder sample to be tested 2 / g);
[0019] (3) Calculate the thickness d (nm) of the LFP material coating layer according to the following formula: d = C% × V × 10 -6 / S×10 9 , where V is the true volume of the carbon layer, 2.2 cm 3 / g.
[0020] Preferably, in the above-mentioned method for detecting the integrity of the carbon coating of the lithium iron phosphate material, the conductivity σ (S / m) is tested using a conductivity meter.
[0021] Preferably, in the above-mentioned method for detecting the integrity of the carbon coating of the lithium iron phosphate material, the setting test parameters of the conductivity σ (S / m) are: 6-10MPa, step 2; 10-20MPa, step 5; 20-160MPa, step 10.
[0022] Preferably, in the above-mentioned method for detecting the carbon coating integrity of lithium iron phosphate material, the carbon content value C% is tested using a carbon content testing device.
[0023] Preferably, in the above-mentioned method for detecting the integrity of the carbon coating of the lithium iron phosphate material, the carbon content testing equipment is a high-frequency infrared carbon-sulfur analyzer.
[0024] Preferably, in the above-mentioned method for detecting the integrity of carbon coating of lithium iron phosphate material, the specific surface area S (cm 2 / g) was tested using a specific surface area tester.
[0025] Preferably, in the above-mentioned method for detecting the integrity of the carbon coating of the lithium iron phosphate material, the specific surface area tester is a NOVA touch LX4 specific surface area tester.
[0026] Preferably, in the above-mentioned method for detecting the integrity of carbon coating of lithium iron phosphate material, the d≥1nm.
[0027] Preferably, in the above-mentioned method for detecting the carbon coating integrity of lithium iron phosphate material, the coating integrity index R≤0.5.
[0028] Beneficial effects:
[0029] The above-mentioned detection method for the carbon coating integrity of lithium iron phosphate materials tests the carbon content and specific surface area of the material. The theoretical carbon coating thickness of the material can be obtained through simple mathematical calculations. The coating integrity index can be obtained by combining the conductivity result. The material integrity evaluation can be measured through clear and intuitive numerical values. The three different test results of carbon content, conductivity and specific surface area are cleverly integrated, and the evaluation is standardized using a simple and easy calculation formula to reduce the influence of subjective factors, so that the evaluation and screening of materials have standards to rely on and criteria to follow. The analysis method of the carbon coating thickness and coating integrity of LFP materials is changed from the existing electron microscope observation method with high labor and financial consumption to a carbon content, conductivity and specific surface area test calculation method. The evaluation process is efficient, low-cost, and the evaluation results are more comprehensive and accurate. It can be used to effectively evaluate and screen LFP materials, significantly improve the evaluation efficiency and quality, and provide an important reference for the evaluation and screening of materials. At the same time, it can also reversely evaluate the advantages and disadvantages of process flows such as battery production. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 is the Coulomb efficiency curve;
[0031] Figure 2 It is the cycle capacity retention rate curve. DETAILED DESCRIPTION
[0032] In order to enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention is further described in detail below in conjunction with specific implementation methods.
[0033] Example 1
[0034] Three LFP cathode materials A, B, and C were evaluated and screened. The detection method for the carbon coating integrity of lithium iron phosphate materials is as follows:
[0035] 1. Test the carbon content of three raw materials
[0036] 1.1 Equipment and Instruments
[0037] High frequency infrared carbon and sulfur analyzer, analytical balance, high purity oxygen (≥99.999%), crucible, etc.
[0038] 1.2 Testing Process
[0039] (1) Open the valves of the oxygen cylinder and nitrogen cylinder, turn on the power switch of the equipment, turn on the computer host, open the carbon and sulfur analyzer operating software, wait for the equipment to stabilize, click "Tools"-"Signal Long-term Stability Monitoring" on the software operation interface, select oxygen, observe the voltage curve of C, and start the test after the voltage fluctuation stabilizes.
[0040] (2) Take a clean crucible and place it on the balance tray, peel it, then add the sample, click "Settings" - "Analysis Parameters Settings", and change the sample name to A; after the balance reading stabilizes, press the "Enter" key on the balance to automatically record the sample mass (0.1g); after removing the crucible and adding flux, place the crucible on the carbon-sulfur analyzer, press the analysis key in the carbon-sulfur analyzer software, and the test will start automatically.
[0041] (3) Repeat the above operation to test samples B and C respectively. (Each sample is tested twice)
[0042] (4) After testing the standard sample within the selected range for more than 2 times, select the standard curve, click "Calibration" - "Correction" - "OK", select the "*" in "Carbon Calibration Value (%)" behind the standard curve, and then click "Correction Carbon" to complete the calibration of the standard curve; return to the main interface, select the sample curve to be tested, right-click - click "Recalculate", take the average value to obtain the carbon content values of samples A, B, and C to be tested, and the test results are shown in Table 2.
[0043] 2. Specific surface area (BET) test of three raw materials
[0044] 2.1 Equipment, instruments, and reagents
[0045] NOVA touch LX4 specific surface area tester; analytical balance, accuracy 0.0001g; 9mm glass tube; 6mm filling rod; NOVA touch LX4; liquid nitrogen.
[0046] 2.2 Testing Process
[0047] (1) Weigh the glass tube to be used and record its weight as m1. Fill the glass tube with the sample A to be tested.
[0048] (2) Carefully open the heating pack, insert the sample tube and fix it at the degassing port. Then fix the heating pack with a hanging hook. Click the heating icon on the instrument touch screen, then click the arrow icon to select the appropriate degassing program, and click Start Selection, as shown in Table 1.
[0049] Table 1 Degassing procedures selected for testing
[0050] Do you need a dust plug? Heating program name Filling rod Procedural Methods no 0412-200 unnecessary Rise from room temperature to 200°C at 10°C / min, and keep constant temperature for 120 minutes
[0051] (3) When the temperature of the heating pack is less than 80°C, remove the sample from the degassing port, remove the heating pack, weigh the sample, and record the weight m2. m2-m1=3g is the net weight of the sample (sample weight).
[0052] (4) Place the degassed sample in the analysis station, add a certain amount of liquid nitrogen into the Dewar flask (5 cm from the flask mouth), place it on the lifting plate, and close the hatch.
[0053] (5) Click NOVA Analysis Parameters and confirm that all parameters in Common are correct.
[0054] (6) Click Stn1, click Admin to set a file name; click Points to set the analysis point, and click Add to add an analysis point.
[0055] (7) Click Analysis to set whether to use a filler rod and select 9mm w / o rod.
[0056] (8) Click Reporting to set the material type of the test sample. Select Oxygen-Zeolit for Adsorbent Solid.
[0057] (9) The analysis method for other analysis stations is the same as the setting method for analysis station 1. Check the analysis station to be used. After the setting is completed, click Strat to pop up a window. Enter the sample ID and sample weight and then click Start to start the analysis.
[0058] (10) Repeat the above steps to analyze samples B and C.
[0059] (11) Read the data automatically displayed by the instrument and use the BET equation to calculate the specific surface area of the sample, as shown in Table 2.
[0060] 3. Conductivity test on three raw materials
[0061] 3.1 Equipment and Instruments
[0062] Powder resistivity & compaction density meter, analytical balance.
[0063] 3.2 Testing Process
[0064] (1) Power on the device, turn on the power, and open the software.
[0065] (2) Click "Experiment Configuration" in the upper left corner of the software; set the test parameters to: 6-10MPa, step 2; 10-20MPa, step 5; 20-160MPa, step 10. Check "Enable" and click "Save and Exit". Open the equipment protection door, place the fixture on the test bench, close the protection door; click "Thickness Reset" on the top of the software, and click "OK" when completed.
[0066] (3) Weigh the sample A to be tested on a balance and record the sample weight as m1. Remove the gasket on the fixture, pour the powder into the fixture cavity, and weigh the residual mass of the weighing paper as m2; place the fixture in the pre-vibration instrument to vibrate the powder; remove the fixture, cover it with the upper gasket, open the protective door, place the fixture with the sample on the test bench, and close the protective door; click "Start Experiment" on the top of the software, enter the mass m1-m2=0.5g, and click "OK" to wait for the test to complete. After the software completes the test, remove the fixture; place the fixture horizontally into the cavity of the automatic mold removal tooling; withdraw the push rod and remove the fixture.
[0067] (4) Repeat the above operation to test samples B and C respectively. The test results are shown in Table 2.
[0068] 4. The carbon coating thickness and carbon coating integrity of the three materials were calculated according to formulas (1) and (2), as shown in Table 3.
[0069] The theoretical coating thickness d (nm) of the LFP material to be evaluated is calculated according to formula (1):
[0070] d=C%×V×10 -6 / S×10 9 (1), V: true volume of carbon layer, 2.2 cm 3 / g;
[0071] The coating integrity index R of the LFP material to be evaluated is calculated according to formula (2) (Note: when the theoretical coating layer thickness of the LFP material to be evaluated is d≥1nm, formula (2) is applicable), R=σ / d(2).
[0072] 5. After the three raw materials are made into batteries, the cycle test is carried out to obtain the Coulomb efficiency curve ( Figure 1 ) and cycle capacity retention curve ( Figure 2 ).
[0073] 6. Conclusion
[0074] Among the three materials, C has the highest theoretical film thickness, but the lowest electrical conductivity and the worst carbon coating integrity; A has a medium theoretical film thickness, but the best electrical conductivity and the best carbon coating integrity; B has the lowest theoretical film thickness, but its electrical conductivity performance is not much different from C, and its carbon coating integrity is medium. Therefore, the evaluation results of the coating integrity of the three materials are: A>B>C.
[0075] Combined with the Coulomb efficiency curve ( Figure 1 ), Cycle capacity retention rate curve ( Figure 2 ) It can be seen that the evaluation results obtained by the method of the present invention are consistent with the law presented by the cycle curve. Based on this, the method of the present invention is highly accurate and feasible.
[0076] Table 2 Test results of carbon content, specific surface area (BET) and conductivity of three LFP raw materials
[0077] Sample name Carbon content BET(m2 / g) Conductivity (S / cm) DY-17 1.54% 13.5376 0.2298 P700H 1.19% 11.5748 0.1566 A2C 1.39% 10.8398 0.1522
[0078] Table 3 Calculated carbon coating thickness and coating integrity index
[0079] Sample name Carbon coating thickness / nm Carbon coating integrity index A 2.5 0.0918 B 2.3 0.0692 C 2.8 0.0539
[0080] The above is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the present invention, which are all considered to be within the protection scope of the present invention.
Claims
1. A method for detecting the integrity of carbon coating of lithium iron phosphate material, characterized in that: The specific steps are as follows: (1) Determine the conductivity σ of the LFP powder sample to be tested; (2) Determine the coating thickness d of the LFP powder sample to be tested; (3) Calculate the LFP material coating integrity index R according to the following formula: R = σ / d; (4) The LFP material was evaluated based on the calculation results. The larger the R value, the better the material coating integrity.
2. The method for detecting the carbon coating integrity of lithium iron phosphate material according to claim 1, characterized in that: The coating thickness d in step (2) is a theoretical coating thickness d, which is obtained by the following method: (1) Determine the carbon content C% of the LFP powder sample to be tested; (2) Determine the specific surface area S of the LFP powder sample to be tested; (3) Calculate the thickness d of the LFP material coating layer according to the following formula: d = C% × V × 10 -6 / S×10 9 , where V: 2.2cm 3 / g.
3. The method for detecting the carbon coating integrity of lithium iron phosphate material according to claim 1, characterized in that: The conductivity σ is tested using a conductivity meter.
4. The method for detecting the carbon coating integrity of lithium iron phosphate material according to claim 3, characterized in that: The setting test parameters of the conductivity σ (S / m) are: 6-10MPa, step 2; 10-20MPa, step 5; 20-160MPa, step 10.
5. The method for detecting the carbon coating integrity of lithium iron phosphate material according to claim 2, characterized in that: The carbon content value C% is tested using a carbon content testing device.
6. The method for detecting the carbon coating integrity of lithium iron phosphate material according to claim 5, characterized in that: The carbon content testing equipment is a high-frequency infrared carbon-sulfur analyzer.
7. The method for detecting the carbon coating integrity of lithium iron phosphate material according to claim 2, characterized in that: The specific surface area S is tested using a specific surface area tester.
8. The method for detecting the carbon coating integrity of lithium iron phosphate material according to claim 7, characterized in that: The specific surface area tester is a NOVA touch LX4 specific surface area tester.
9. The method for detecting the carbon coating integrity of lithium iron phosphate material according to claim 1 or 2, characterized in that: The d≥1nm.
10. The method for detecting the carbon coating integrity of lithium iron phosphate material according to claim 1, characterized in that: The coating integrity index R≤0.5.
Citation Information
Cited By
Method for evaluating carbon content in lithium sulfide and application of method
CN119881020A
Evaluation method of lithium iron phosphate surface carbon coating integrity and carbonization degree
CN122217903A